An analysis of traffic flow and control for road safety audits at Jalan Berapit (State Route P131) Bukit Mertajam, Pulau Pinang - Musir A.A.; Ramli M.Z.; Ramlee R.; Abdullah N.H.H.; Albar A.; Hasan D.; Dollah Z. (American Institute of Physics Inc., 2023)
In Malaysia, the increasing rate of the road accident fatalities in rural road has been one of major concern to the authorities and the public. One of the systems that have been implemented to ensure that the roads are achieved the required standards of safety is Road Safety Audit (RSA). RSA is a formal safety examination of an existing and new road by an independent or qualified team. The objectives of the study are to evaluate any potential unsafe features or operational arrangement that may adversely affect the safety of any road user and to justify the risk and severity of crashes that may be attributing to the existing road condition. The focus of study is traffic flow and control which includes the study of traffic signal installation, general traffic management, cross-section and intersection (sight distance). For the RSA inspection, the field study is conducted at Jalan Berapit, Bukit Mertajam which includes the data collection of traffic volumes, spot speed, site inspection and qualitative research questionnaire. The data of questionnaire are analyzed by using SPSS and the site inspection are analyzed by using prioritization method and compared to the Guidelines for the Safety Audit of Roads in Malaysia. 2018 Author(s).